Study of Ki Hadjar Dewantara's educational thinking and its relevance to Kurikulum Merdeka - Aditya Anugrah Dwipratama (Inovasi Kurikulum, 2023)
Education is essential in advancing a nation, especially in building human resources. Teaching and valuable education for shared life is to liberate humans as community members. The Ministry of Education and Culture issued the Kurikulum Merdeka to restore learning due to the COVID-19 pandemic. Curriculum development must consider several foundations, such as philosophical, psychological, sociological, and science and technology foundations. The foundation of the curriculum is essential, and it is intended that the curriculum compiled has a firm footing and foundation. In its journey, the development of the independent curriculum was influenced by various ideas from educational figures, one of which was Ki Hadjar Dewantara. The concepts of Ki Hadjar Dewantara have influenced education development in Indonesia, including curriculum development. This article examines the thoughts of Ki Hadjar Dewantara and their relevance to the independent curriculum. Ki Hadjar Dewantara's ideas are still relevant today in the independent curriculum. Ki Hadjar Dewantara's ideas are used as philosophical, theoretical, and learning principles in the Kurikulum Merdeka. AbstrakPendidikan memegang peran penting dalam memajukan suatu bangsa, terutama dalam membangun sumber daya manusia pada sebuah bangsa. Maksud pengajaran dan pendidikan yang berguna untuk peri-kehidupan bersama ialah memerdekakan manusia sebagai anggota dari persatuan (masyarakat). Kemendikbud mengeluarkan kurikulum merdeka sebagai upaya pemulihan pembelajaran akibat adanya pandemi Covid-19. Pengembangan kurikulum harus memperhatikan beberapa landasan seperti landasan filosofis, landasan psikologis, landasan sosiologis dan landasan IPTEKS. Landasan kurikulum merupakan hal yang sangat penting, hal tersebut bertujuan agar kurikulum yang disusun memiliki pijakan dan landasan yang kuat. Pada perjalanannya pengembangan kurikulum merdeka dipengaruhi oleh berbagai gagasan tokoh pendidikan salah satunya Ki Hadjar Dewantara. Gagasan pemikiran Ki Hadjar Dewantara telah mempengaruhi perkembangan pendidikan di Indonesia termasuk dalam pengebangan kurikulum. Artikel ini menelaah pemikiran Ki Hadjar Dewantara dan relevansinya pada Kurkulum Merdeka. Pemikiran Ki Hadjar Dewantara masih relevan sampai saat ini, pada kurikulum merdeka pemikiran Ki Hadjar Dewantara digunakan sebagai landasan filosofis, landasan teoritis dan prinsip pembelajaran dalam kurikulum merdeka.Kata Kunci: Ki Hadjar Dewantara; Kurikulum Merdeka; landasan pengembangan kurikulum